Printed newspapers and literature. Circulation, exhibition, exchanges. Innovation, editorial practices, poetics (Anclajes, 2022)
Some time ago it was customary to study literature by placing the figures of the author and their literary projects at the center, paying little attention to the collective contexts of publication (unless they were avant-garde magazines), without considering how and where the letters had acquired the material body that requires thinking about them not only in terms of writing but also in terms of their circulation, in terms of readings and appropriations. In recent years, research on literature has increasingly addressed these aspects, providing valuable knowledge to study Latin American literature with perspectives attentive to its materiality and forms of circulation. The dossier Literature, journalism and materiality explores the exhibition strategies, the forms of innovation, the editorial practices and the poetics produced in the intense process of exchanges between the press and literature in Mexico and Argentina during the first half of the 20th century. It shows how the concept of materiality has been expanded, with a variety of significant aspects to think about the periodic forms of production, circulation and consumption of literature.
Keywords: Latin American periodicals; Materiality; Latin American literature; twentieth century